Local genetic patchiness but no regional differences between Indo-West Pacific populations of the dogtooth tuna Gymnosarda unicolor - Bentley, B.; Harvey, Euan; Newman, Stephen; Welch, D.; Smith, A.; Kennington, W. (Inter-Research, 2014)
Physical barriers can have profound impacts on dispersal in marine species. Here, we investigate population structure and levels of relatedness among individuals of the coral reef associated fish, the dogtooth tuna Gymnosarda unicolor, collected from 15 sites across the Indo-West Pacific region. We screened 92 individuals for genetic variation at 13 nuclear microsatellite loci and the cytochrome c oxidase subunit 1 (COI) mitochondrial DNA (mtDNA) gene. We detected no genetic differentiation between ocean basins or between sites within ocean basins, suggesting G. unicolor possesses a highly mobile larval or juvenile stage. In addition, the lack of deep evolutionary mtDNA divergences suggests gene flow was also not limited historically. However, comparisons of relatedness between pairs of individuals revealed that individuals collected from the same site were more related to each other, on average, than individuals collected from different sites. Such patterns are consistent with chaotic genetic patchiness, a possible consequence of high variance in reproductive success and patchy, local recruitment.